Introduction, issue 69 - Mabro, R (Oxford Institute for Energy Studies, 2007)
Oxford Energy Forum is a debating journal and we always welcome letters and comments from readers adding to, qualifying or criticising views expressed in earlier articles. I am pleased that the articles on nuclear energy published in the previous issue have attracted two important responses which add a new dimension to the debate.